Vengeance as Corollary of Social Injustice: A Thematic and Character Analysis of Selected Yorùbá Novels - Adejoke Remi Oluwaseyi-Paul (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
Vengeance has constantly manifested across human social existence and continues to find depiction in many creative productions, Yorùbá novels inclusive. Because of its nature of recycling conflict and violence causing issues, vengeance has contributed immensely to generating social malady. Earlier researchers have focused more on the issues of crime, violence and conflict management aspects of the Yorùbá novels thereby paying lesser attention to issues of vengeance which is the gap this work tends to fill. This work therefore uses Hippolyte Taine’s mirror image approach of sociology of literature. This study applied the qualitative research approach and the interpretive design to examine the cause and implications of vengeance in the three purposively selected Yorùbá novels due to their thematic concern with vengeance which is intended to helping in stemming the tide of vengeance in the society. The novels are: Ojúadé’s Taa L’Ọ̀daràn, Adébọ̀’s Ọ̀dọ́ Ìwòyí, and Owólabí’s Ẹjọ́ọ Taa ni?. This study establishes that injustice is the major cause of vengeance as portrayed by the novelists of the selected novels which is acting as the direct reflection of the human society. Implication of vengeance in this paper includes loss of lives, insecurity and poor health.